2014
DOI: 10.1117/1.jrs.8.083618
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the spectral stability of Libya 4, Libya 1, and Mauritania 2 sites using Earth Observing One Hyperion

Abstract: The objective of this paper is to formulate a methodology to assess the spectral stability of the Libya 4, Libya 1, and Mauritania 2 pseudo-invariant calibration sites (PICS) using Earth Observing One (EO-1) Hyperion sensor. All the available Hyperion collections, downloaded from the Earth Explorer website, were utilized for the three PICS. In each site, a reference spectrum is selected at a specific day in the vicinity of the region of interest (ROI) defined by Committee on Earth Observation Satellites (CEOS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
1
5
0
1
Order By: Relevance
“…Our results appear consistent with other studies that found Hyperion TOA radiances to be spectrally stable within 5% in the VNIR and 10% in the SWIR [27]. Figure 2 displays trends, CV, and R 2 (p-val < 0.01) for reflectance in 172 calibrated bands retrieved with AT, AC and F 135 models.…”
Section: A Hyperion Trend Analysissupporting
confidence: 90%
See 1 more Smart Citation
“…Our results appear consistent with other studies that found Hyperion TOA radiances to be spectrally stable within 5% in the VNIR and 10% in the SWIR [27]. Figure 2 displays trends, CV, and R 2 (p-val < 0.01) for reflectance in 172 calibrated bands retrieved with AT, AC and F 135 models.…”
Section: A Hyperion Trend Analysissupporting
confidence: 90%
“…These results suggest Libya-4 is an ideal location to monitor the impacts of orbital 79 precession on Hyperion data products. Other studies have examined the Hyperion TOA VSWIR 80 temporal trend in the Libya-4 PICS and found it to be stable within 2.5 -5 % in most spectral 81 bands [27]. However, this is the first study, to our knowledge, to examine Hyperion's surface 82 reflectance trends associated with EO-1's rapid orbit degradation years (2014+).…”
Section: Index Terms-pseudo-invariant Calibration Site (Pics) Land Surface Imaging (Lsi) Eo-1 Hyperion Surface Reflectance Libya-4 Time-smentioning
confidence: 83%
“…However, this landcover classification applies to many current PICS extensively used for sensor radiometric calibration and performance analysis, such as Libya 4, Mauritania 1, and Algeria 1 [5,8,21,22]. Choi et al [41] studied the spectral stability of the Libya 4, Libya 1 and Mauritania 2 PICS using average deviation (AD) and spectral angle mapper (SAM) where average deviation is the absolute reflectance difference and SAM is the spectral angle between the test and reference spectrum [42,43]. This is the earliest attempt to study the spectral similarity of PICS and in this study, they found that ROIs chosen parallel to the along-track direction were spectrally stable for spectral angle mapper values up to ±2 degrees, with an average deviation of ±1.7% in reflectance scale.…”
Section: Discussionmentioning
confidence: 99%
“…It is located in the Great Sand Sea (28.55 • N, 23.39 • E) at an average height of 118 m above sea level. The study area was covered by unvegetated sand dunes and it usually had high atmospheric stability with low aerosol content as well as a low presence of cloudiness [24].…”
Section: Study Areamentioning
confidence: 99%